PENGARUH FASILITAS BELAJAR DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR PESERTA DIDIK JURUSAN OTOMATISASI DAN TATA KELOLA PERKANTORAN SMK KARTIKA 1-2 PADANG DI MASA PANDEMI COVID-19 - Eriyen Gustina Ulfa; Armiati Armiati (Jurnal Salingka Nagari, 2022)
This study aims to determine: 1) the effect of learning facilities and the use of learning media on students' interest in learning in the Department of Automation and Office Governance at SMK Kartika 1-2 Padang. 2) The effect of learning facilities on student interest in the Department of Automation and Office Governance at SMK Kartika 1-2 Padang. 3) The influence of the use of learning media on student interest in the Department of Automation and Office Governance at SMK Kartika 1-2 Padang. This type of research is descriptive quantitative using SPSS version 21 program. The population in this study amounted to 90 with total sampling technique. The results of the research that have been carried out are 60.3% which can be concluded that the influence of learning facilities and the use of learning media on learning interest of students in the Department of Automation and Office Management at SMK Kartika 1-2 Padang.